2014
DOI: 10.1002/2013gc005087
|View full text |Cite
|
Sign up to set email alerts
|

Strain field analysis on Montserrat (W.I.) as tool for assessing permeable flow paths in the magmatic system of Soufrière Hills Volcano

Abstract: Strain dilatometers have been operated on the volcanic island of Montserrat (West Indies) for more than a decade and have proven to be a powerful technique to approach short-term dynamics in the deformational field in response to pressure changes in the magmatic system of the andesitic dome-building Soufrière Hills Volcano (SHV). We here demonstrate that magmatic activity in each of the different segments of the SHV magmatic system (shallow dyke-conduit, upper and lower magma chambers) generates a characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 88 publications
2
32
1
Order By: Relevance
“…Recent observations of degassing and deformation at volcanoes demonstrate that transport can be rapid in igneous mush systems. For example, episodes of magmatic fluid transport from depths of at least 10 km are illustrated by volumetric strain data and SO 2 gas fluxes associated with eruptive activity at the andesitic Soufrière Hills volcano on Montserrat (Gottsmann et al, 2011;Hautmann et al, 2014;Christopher et al, 2015). Transport speeds of several meters per second are indicated within the Soufrière Hills volcano mush region and are consistent with transport through transient fracture systems.…”
Section: Fluid Transfer Regimesmentioning
confidence: 82%
“…Recent observations of degassing and deformation at volcanoes demonstrate that transport can be rapid in igneous mush systems. For example, episodes of magmatic fluid transport from depths of at least 10 km are illustrated by volumetric strain data and SO 2 gas fluxes associated with eruptive activity at the andesitic Soufrière Hills volcano on Montserrat (Gottsmann et al, 2011;Hautmann et al, 2014;Christopher et al, 2015). Transport speeds of several meters per second are indicated within the Soufrière Hills volcano mush region and are consistent with transport through transient fracture systems.…”
Section: Fluid Transfer Regimesmentioning
confidence: 82%
“…This progress allows to characterize the geometry of magmatic plumbing systems underlying volcanoes in terms of reservoir shapes, depths and numbers. In particular, at some specific volcanoes, deep magmatic reservoirs, which had been ignored so far, are evidenced (e.g., Elsworth et al, 2008;Chadwick et al, 2011;Bagnardi and Amelung, 2012;Hautmann et al, 2014;Tiampo et al, in press). However, most of the models used to interpret geodetic data are kinematic and cannot provide information on the pressure within the magmatic system, which is the key parameter to control the timing of magma reservoir rupture as well as the ability of magma to reach the surface and thus to feed an eruption.…”
Section: Introductionmentioning
confidence: 99%
“…A typical conduit radius of around 15 m has been inferred from the size of extruded andesitic spines [Voight et al, 1999;Sparks et al, 2000;Melnik and Sparks, 2002] though spines of 25 m radius have also been reported . Volumetric strain data have provided important insights on plumbing system dynamics beneath SHV during explosive activity [Chardot et al, 2010;Linde et al, 2010;Voight et al, 2010;Hautmann et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric strains induced by pressure transients in the conduit are thought to be masked when lower sections of the plumbing system are involved in explosions; this has been shown by strain modeling of the various system components of the Soufrière Hills Volcano [Hautmann et al, 2014;Odbert et al, 2014]. Consequently, the conduit dimensions consistently used in the literature have not been tested by strain modeling [Chardot et al, 2010;Linde et al, 2010;Voight et al, 2010;Gottsmann et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation